Terebellidae (Polychaeta) from the Mexican Caribbean with description of four new species - Londoño-Mesa, Mario H.; Carrera-Parra, Luis F. (Zootaxa, 2005)
Twenty species of Terebellidae Grube, 1850 were recorded and characterized from the Mexican Caribbean, four were newly described: Polycirrus holthei sp. nov., Loimia salazari sp. nov., Neoamphitrite glasbyi sp. nov., and Terebellobranchia mchughae sp. nov. The other species recorded were Lysilla sp., Amphitritides bruneocomata (Ehlers, 1887), Eupolymnia crassicornis (Schmarda, 1861), Eupolymnia nebulosa (Montagu, 1818), Loimia medusa (Savigny, 1818), Loimia minuta Treadwell, 1929, Nicolea modesta Verrill, 1900, Paraeupolymnia carus Young & Kritzler, 1987, Pista palmata (Verrill, 1873), Pista cf. quadrilobata (Augener, 1918), Spinosphaera carrerai Londoño-Mesa, 2003, Spinosphaera hutchingsae Londoño-Mesa, 2003, Streblosoma hartmanae Kritzler, 1971, Terebella verrilli Holthe, 1986, and Thelepus setosus (de Quatrefages, 1865). Materials from the Mexican Caribbean are compared with populations from the Grand Caribbean Region and elsewhere, and with descriptions available in the literature. A taxonomic key for the terebellids recorded from the Grand Caribbean Region is provided.